Dissecting study groups - Anders Lerche Møller; Emil Smith; Peter Musaeus (Dansk Universitetspaedagogisk Tidsskrift)
This study investigates the dynamics of study groups among second-semester medical students enrolled in a gross anatomy course at Aarhus University, Denmark, during the autumn of 2018. Study groups served as organising units that had beneficial motivational, learning, and social effects. They provided accountability, academic support, and progress monitoring. Shared beliefs within these groups, influenced by near-peers, shaped the social norms for studying. The study suggests enhancing the effectiveness of study groups by targeting these beliefs through formal education of social role models, such as student teachers. Recognising the limitations of homogenous groups, the paper advocates for diverse peer groups to develop teamwork and higher order thinking skills. These findings underscore the importance of considering both academic and psychological aspects of group dynamics to improve student wellbeing and academic performance.